2016
DOI: 10.1186/s13054-016-1309-2
|View full text |Cite
|
Sign up to set email alerts
|

Fluid management of the neurological patient: a concise review

Abstract: Maintenance fluids in critically ill brain-injured patients are part of routine critical care. Both the amounts of fluid volumes infused and the type and tonicity of maintenance fluids are relevant in understanding the impact of fluids on the pathophysiology of secondary brain injuries in these patients. In this narrative review, current evidence on routine fluid management of critically ill brain-injured patients and use of haemodynamic monitoring is summarized. Pertinent guidelines and consensus statements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
74
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 82 publications
1
74
0
2
Order By: Relevance
“…Ibrahim and colleagues also reported colloid administration and positive fluid balance were associated with poor outcome [ 61 ]. The findings are consistent with conclusions of van der Jagt’s review, three years later, of literature on fluid management of critically-ill brain injured patients [ 63 ]. He concluded that the best hypothesis was that these patients should be kept euvolemic through administration of non-colloid fluids in an attempt to maintain normal physiologic conditions.…”
Section: Critical Care Management Of Asahsupporting
confidence: 91%
“…Ibrahim and colleagues also reported colloid administration and positive fluid balance were associated with poor outcome [ 61 ]. The findings are consistent with conclusions of van der Jagt’s review, three years later, of literature on fluid management of critically-ill brain injured patients [ 63 ]. He concluded that the best hypothesis was that these patients should be kept euvolemic through administration of non-colloid fluids in an attempt to maintain normal physiologic conditions.…”
Section: Critical Care Management Of Asahsupporting
confidence: 91%
“…Whether this imbalance in fluid management studies between different types of brain injuries is a reflection of differences in clinical relevance of fluid management is not clear. [1] Further randomised controlled trials in the future are essential in SAH and TBI patients who are critical and need long term ICU stay to elucidate and define the role and relevance of the ROSE concept in neuroanaesthesia and neurocritical care.…”
Section: Resultsmentioning
confidence: 99%
“…The use of hypotonic fluids can lead to tissue oedema, which results in oxygen diffusion and cerebral blood flow (CBF) impairments. [1] Fluid management Journal of Neuroanaesthesiology and Critical Care | Vol. 4 • Issue 1 • Jan-Apr 2017 | fluid balance and fluid overload and the outcomes in critically ill adults.…”
Section: Introductionmentioning
confidence: 99%
“…Whether hydration changes in the experimental group resulted from intravenous fluid administration or from increased water and ice intake was thus impossible to determine. 21,38 Positive Clinical Outcomes and Negative Clinical Indicators. The research SLP recorded positive and negative clinical outcomes daily during the business week.…”
Section: Figure 1 Aspiration Precaution Oral Care Program Implementatmentioning
confidence: 99%